Comparison of Histomorphometric Measurements of Equine Sternal Cancellous Bone with Bone from other Skeletal Sites - Désévaux, C.; Laverty, S.; Martineau-Doizé, B. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
Histomorphometric analysis of bone biopsy specimens in humans is a reliable techniqu e which provides information on bone status and turnover. A techniqu e of sternal biopsy has been recently developed in “standin g horses” . The purpose of the present study was to demonstrate that the histomorphometric analysis of sternal cancellous bone was representative of other skeletal sites in horses.Post-mortem cancellous bone samples were obtained from the sternum, 12th rib, ilium, 1st lumbar vertebra and the tibia, of seven adult horses and embedded in methylmethacrylate. Sections, 7 μm thick, were cut and were stained with Goldner’s green trichrome. Histomorphometric parameters were measured by a semi-automated method. Sections from the sternum were qualitativel y similar to those from the rib, ilium and vertebra. Histomorphometric measurements were easily performed on the sternal, ilium, rib and vertebral sections. The tibial sections were not suitable for evaluation. The sternal histomorphometric parameters of bone formation and resorption were overall representative of those from other skeletal sites.The present study demonstrated that sternal cancellous bone is acceptable for bone histomorphometry in horses as it reflects overall skeletal osseous activity.This study compares qualitatively and quantitatively cancellous bone from the sternum, 12th rib, ilium, first lumbar vertebra and the tibia of seven adult horses. Sternal cancellous bone is acceptable for bone histomorphometry and reflects overall skeletal osseous activity.
Keywords: Bone; cancellous bone; histomorphometry; biopsy; horse